Outdoor light at night, genetic predisposition and type 2 diabetes mellitus: a prospective cohort study - Xu,Z; Jin,J; Yang,T; Wang,Y; Huang,J; Pan,X; Frank,K; Li,G (Environmental Research, 2023)
BackgroundAccording to animal and human epidemiologic studies, exposure to outdoor light at night (LAN) may cause circadian disruption, which may disturb sleep quality and lead to incident type 2 diabetes mellitus (T2DM).MethodsWe followed 283,374 persons from 2006 through 2020. Outdoor LAN exposure was estimated using satellite data for individual address with 500 m2 scale buffer during follow-up. Incidence of T2DM was confirmed by hospital inpatient records. We identified potential confounders by a directed acyclic graph, including demographic, genetic, individual and regional level socioeconomic status, and environmental risk factors, and calculated hazard ratios (HRs) and 95% confidence intervals (CIs) through time-varying Cox proportional hazard model. Furthermore, we examined the association of outdoor LAN with a defined health sleep scores and moderation of genetic predisposition and shift work on the relationship of outdoor LAN and incident T2DM.ResultsWe identified 7,775 incident T2DM cases over 3,027,505 person-years. Higher outdoor LAN exposures were significantly associated with higher risk of T2DM. The estimated HR for incident T2DM with an interquartile range (IQR: 11.22 nW/cm2/sr) increase in outdoor LAN was 1.05 (95%CI: 1.01, 1.09) in the fully adjusted model. Participants who lived in the highest quarter of outdoor LAN area were more likely to develop T2DM (HR: 1.14,95%CI: 1.02, 1.27). Besides, those who were exposed to higher levels of outdoor LAN had poorer sleep quality. No moderation role of PRS on outdoor LAN-induced T2DM observed both on the multiplicated and additive scale. The hazards of outdoor LAN were observed in those who never owned a night shift work.ConclusionAlthough further work is required to clarify potential mechanisms, our findings indicate that exposure to residential outdoor LAN may contribute to T2DM risk and low sleep quality.